Meaning of Lesung in Thek Thok Gung Dance Work - Astuti, Suryani Dwi; Widyawati, Setya Widyawati (Universitas Negeri Semarang, 2025)
Thek Thok Gung is a new creation dance created by Suryani Dwi Astuti and Lina Puspitasari inspired by the activity of togetherness behind the beating of mortar. The activity referred to in this dance work is the activity of togetherness in the ritual of searching for missing people since pre-colonial times. In this dance work, the use of lesung becomes a bridge between practical and symbolic functions, between work and celebration, between the past and the present. This research aims to describe the form and meaning of lesung in Thek Thok Gung dance work. This research uses a qualitative descriptive method. The theory used to answer the problem of form uses the theory of form according to Y. Sumandiyo Hadi. The disclosure of meaning in this study uses the theory of “Ëstetika Paradoks” by Jacob Sumardjo. This research uses a choreographic approach. The research steps taken in collecting data were obtained through observation, interviews, and literature studies. The results show that Thek Thok Gung dance work consists of elements of dance form, namely dance title, dance theme, type or type of dance, mode or way of presentation, dancers, movement, space, dance music, makeup and clothing, property, and lighting. The meaning of beating the mortar is a symbol and ritual that is believed to affect reality. Its aesthetics are not in the form of visual or sound beauty, but in symbolic and spiritual functions.